Psychometric evaluation of the self-undermining scale in South Africa using the Rasch model - Sergio L. Peral (African Journal of Psychological Assessment)
The self-undermining scale is used to assess employee behaviours that undermine job performance, including making mistakes, creating conflict, creating confusion and creating a backlog in work tasks. To date, its psychometric properties have not been thoroughly investigated using item-response theory applications, especially in South Africa. Applying the Rasch Rating Scale Model, this study aimed to investigate the reliability and internal validity of the self-undermining scale, including item fit and rating scale functionality. Data were collected from 318 South African employees using a non-experimental, cross-sectional survey design. The instrument demonstrated unidimensional scaling with Cronbach’s alpha and person separation values of 0.77 and 1.57, respectively. Item and category fit statistics showed satisfactory fit to the Rasch model, with only one item warranting further attention. Some refinements regarding item wording and rating scale optimisation are provided.